Microstructural evolution and mechanical properties of β-type Ti10Nb10Zr alloy produced by metal injection molding - (:unkn) unknown (European Powder Metallurgy Association (EPMA), 2016)
This paper describes the microstructural and mechanical properties of injection molded of Ti10Nb10Zr alloy. Ti, Nb and Zr powders were used for this study. In the first experiments elemental metal powders of Ti, Nb and Zr were mixed according to the desired composition of Ti10Nb10Zr. Mixed powders were injection molded with wax-based binder. The critical powder loading for injection molding was 55 vol.%. Binder debinding was performed in solvent and thermal method under high purity argon atmosphere. After debinding the samples were sintered at different temperatures and times in vacuum (10-5 mbar). The performances of the sintered parts were characterized using tensile testing, hardness testing, optical microcopy and scanning electron microscopy. The strengths and weaknesses of the test conditions have been analyzed from the densification behavior, microstructure, and mechanical properties.
Keywords: Mechanical Properties; Powder Injection Molding; Ti alloy